The methodology for designing accessible public transportation: The Czech experience - Matuška, Jaroslav (Transport, 2010)
This is an attempt to ensure an effective process for creating a barrier‐free environment. It is necessary, within the scope of the methodological procedure, to analyse the whole system, search for critical areas and eliminate or prevent them when applying basic and specific properties of the previously defined elementary items. An essential pre‐condition for creating an accessible built environment for everyone is knowledge of effective legislation and technical standards and successful application by all responsible persons. First published online: 27 Oct 2010